Immunomodulatory effects of Lactobacillus biogenic administration in dogs - Junro Hayasaka; Yuka Nunomura; Miki Omura; Yukie Katayama; Tomoko Yokota; Nanako Osawa; Shinji Makino; Tetsuya Mizutani; Tsuyoshi Uchide; Yoshiteru Murata (The Japanese Journal of Veterinary Research, 2021)
[Abstract] Lactobacillus biogenics were administered to four dogs for 56 days. The regulatory T cell (Treg) count was found to be increased in all four dogs on 56 days. On day 112, 56 days after completion of Lactobacillus probiotic administration, the percentage of Tregs was found to be decreased in three dogs. Plasma IgA levels tended to increase after stopping Lactobacillus administration. Metagenomic analysis of bacterial flora found in dog feces revealed that Firmicutes, Proteobacteria, Bacteroidetes, and Fusobacteria were predominantly found in all 4 dogs. Analysis of fecal microbiomes of species level on day 56 showed that 99 % members of genus Prevotella belonged to species copri. This study demonstrates some of the immunomodulatory effects of Lactobacillus probiotics on dogs.